(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study explores the perceptions of English as a Foreign Language (EFL) teachers regarding the use of Artificial Intelligence (AI)-based tools in vocational and senior high schools in Samarinda, East Kalimantan. The rapid growth of AI in education presents both opportunities and challenges, particularly in language teaching. This qualitative research employs a case study approach involving seven English as a Foreign Language (EFL) teachers. Data were collected through semi-structured interviews and analyzed using a thematic analysis approach. The findings indicate that most teachers perceive AI as a supportive tool in instructional material development and administrative efficiency. However, they emphasize that AI cannot replace the human role in the teaching process. The teachers expressed concerns about students’ overdependence on AI, ethical use, and the importance of adapting AI-generated content to suit learners’ needs. They also highlighted the need for professional development, especially for senior educators, to ensure responsible and effective integration of AI in the classroom. This study contributes to the understanding of how AI is perceived in underrepresented educational contexts and underscores the need for balanced implementation strategies that combine pedagogical considerations with technological innovation. It also recommends continuous teacher training aligned with clear ethical guidelines so that AI truly enhances rather than diminishes the quality of language learning.